Finding the optimal parameters for the steam explosion process of hay. - MarouÅ¡ek, Josef (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Combining biochemical principles and mathematical methods were defined optimal extrusion (steam explosion) process conditions for pelleted hay resulting in maximal cumulative production of biogas (CBGP). Operating experiments were conducted on a continuous modifiable extruder. Variable parameters, the reaction time, pressure and dry mass were compared and optimized. An assumption that longer reaction time, lower dry mass and higher operating pressure results in higher yields of biogas were confirmed only in defined pressure range. Critical conditions, from where the yield starts to decrease due to inhibitors formations were also modeled. It was found that the optimal process conditions were in the neighborhood of pressure 1.3 MPa, reaction time 7 minutes and 8% of dry mass resulting in 405 m3 of biogas (52.3% CH4) per ton of dry mass.